Benchmarking New Zealand's frontier firms - Guanyu Zheng; Hoang Minh Duy; Gail Pacheco (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2021)
New Zealand has experienced poor productivity performance over the last two decades. Factors often cited as reasons behind this are the small size of the domestic market and distance to international partners and markets. While the distance reason is one that is fairly insurmountable, there are a number of other small advanced economies that also face similar domestic market constraints. This study compares the relative performance of New Zealand's firms to those economies using novel cross-country microdata from CompNet. We present stylised facts for New Zealand relative to the economies of Belgium, Denmark, Finland, Netherlands and Sweden based on average productivity levels, as well as benchmarking laggard, median and frontier firms. This research also employs an analytical framework of technology diffusion to evaluate the extent of productivity convergence, and the impact of the productivity frontier on non-frontier firm performance. Additionally, both labour and capital resource allocation are compared between New Zealand and the other small advanced economies. Results show that New Zealand's firms have comparatively low productivity levels and that its frontier firms are not benefiting from the diffusion of best technologies outside the nation. Furthermore, there is evidence of labour misallocation in New Zealand based on less labour-productive firms having disproportionally larger employment shares than their more productive counterparts. Counter-factual analysis illustrates that improving both technology diffusion from abroad toward New Zealand's frontier firms, and labour allocation across firms within New Zealand will see sizable productivity gains in New Zealand.
urn:nbn:de:gbv:3:2-133442
Keywords: L25; O33; O47; 330; labour productivity; productivity convergence; resource allocation